The Effects of Climate Change on Interregional Electricity Market Dynamics on the U.S. West Coast. Issue 12 (15th December 2021) - Hill, Joy; Kern, Jordan; Rupp, David E.; Voisin, Nathalie; Characklis, Gregory
Abstract: The United States (U.S.) West Coast power system is strongly influenced by variability and extremes in air temperatures (which drive electricity demand) and streamflows (which control hydropower availability). As hydroclimate changes across the West Coast, a combination of forces may work in tandem to make its bulk power system more vulnerable to physical reliability issues and market price shocks. In particular, a warmer climate is expected to increase summer cooling (electricity) demands and shift the average timing of peak streamflow (hydropower production) away from summer to the spring and winter, depriving power systems of hydropower when it is needed the most. Here, we investigate how climate change could alter interregional electricity market dynamics on the West Coast, including the potential for hydroclimatic changes in one region (e.g., Pacific Northwest (PNW)) to "spill over" and cause price and reliability risks in another (e.g., California). We find that the most salient hydroclimatic risks for the PNW power system are changes in streamflow, while risks for the California system are driven primarily by changes in summer air temperatures, especially extreme heat events that increase peak system demand. Altered timing and amounts of hydropower production in the PNW do alter summer power deliveries into California but show relatively modest potential to impact prices and reliability there. Instead, our results suggest future extreme heat in California could exert a stronger influence on prices and reliability in the PNW, especially if California continues to rely on its northern neighbor for imported power to meet higher summer demands. Plain Language Summary: Electric power systems are already strongly influenced by extreme weather, and climate change could make this problem worse. In this study, we explore how long‐term shifts in water availability and higher air temperatures could impact supply and demand for electricity in the West Coast region of the United States, and how interactions between two interconnected parts of the West Coast grid (the Pacific Northwest and California) could change as well. We focus on measuring impacts to the grid in terms of reliability (frequency of electricity shortfalls, or blackouts) and wholesale electricity prices. We find that shifts in water availability are likely to be the strongest influence on the Pacific Northwest, while increases in air temperatures are likely to be the strongest influence in California. We hypothesized that altered water availability in the Pacific Northwest could impact California too, through reduced summer deliveries of hydropower. However, our evidence points to future excessive heat in California as the major regional influence, which "pulls" more electricity from the Pacific Northwest, causing price and reliability impacts. Key Points: The U.S. West Coast power system is vulnerable to altered streamflow patterns and air temperature increases caused by climate change Regional power systems are most sensitive to altered streamflows in the Pacific Northwest and air temperature changes in California, respectively Results show that climate‐related impacts in one regional power system can spill over to others in complex ways